TYPES OF REMODELING VESSELS OF DIFFERENT CALIBER IN ARTERIAL HYPERTENSION - Марина Петровна Задорожная; Владимир Валентинович Разумов (Медицина в Кузбассе)
Arterial hypertension is inevitably accompanied by remodeling of the heart and blood vessels, the study of which is characterized by the ambiguity of the research methods that prevent understanding of this phenomenon as a single process in the cardiovascular system.